The Role of Price Perceptions, Product Quality, and Brand Image on Purchasing Decisions - Prayuda, Rafie Zaidan (AGUSPATI Research Institute, 2024)
This research examines the influence of product quality, price perception, and brand image on purchases. The dependent and independent variables in this research are product quality, price perception, and brand image. Descriptive and quantitative methods were used in this research. The use of non-probability and purposeful sampling was used in this study. There were 87 participants in this study who had purchased the product. The SmartPLS test was used in this investigation. Based on the findings, 1) Purchasing decisions are influenced by the quality of a product. 2) When it comes to making purchases, price perception plays a role. 3) Purchasing decisions are influenced by the image of a brand.